Hypoglycemic and H2O2-induced oxidative injury protective effects and the phytochemical profiles of the ethyl acetate fraction from Radix Paeoniae Alba - Zhang, Lu; Peng, Chun-yan; Wang, Pei-xin; Xu, Linju; Liu, Jia-hui; Xie, Xing; Lu, Ling; Tu, Zong-cai (Frontiers in Nutrition, 2023)
Radix Paeonia Alba (RPA) is often used as food and medicine. The study aimed to enrich and identify the antioxidant and hypoglycemic bioactive compounds from RPA. Results indicated that ethyl acetate fraction (EAF) showed the highest total phenolics content, DPPH·, ABTS·+ scavenging ability, and α-glucosidase inhibition ability (IC50=7.27 μg/mL). EAF could alleviate H2O2-induced oxidative stress in HepG2 cells by decreasing MDA and ROS levels, improving cells apoptosis, increasing enzyme activity of GPX-Px, CAT, SOD, Na+/K+-ATP, Ca2+/Mg2+-ATP, and stimulating T-AOC expression, which also enhanced the glucose uptake of insulin resistance HepG2 cells. In addition, EAF significantly reduced the fast blood glucose and improved glucose tolerance in diabetic mice. HPLC-QTOF-MS/MS analysis displayed that procyanidin, digallic acid isomer, methyl gallate, tetragalloylglucose isomer, dimethyl gallic acid and aeoniflorin were the major compounds in EAF. These founding are meaningful for the application of EAF in medicinal or food industry to prevent and treat oxidative stress and diabetes mellitus.